Early Rapid Decline in Kidney Function in Medically Managed Patients With Atherosclerotic Renal Artery Stenosis. Issue 11 (4th June 2019) - Cooper, Emily L.; Xie, Yanmei; Nguyen, Hanh; Brewster, Pamela S.; Sholl, Haden; Sharrett, Megan; Ren, Kaili; Chen, Tian; Tuttle, Katherine R.; Haller, Steven T.; Jamerson, Kenneth; Murphy, Timothy P.; et al.
Abstract : Background: Early rapid declines of kidney function may occur in patients with atherosclerotic renal artery stenosis with institution of medical therapy. The causes and consequences are not well understood. Methods and Results: Patients enrolled in the medical therapy–only arm of the CORAL (Cardiovascular Outcomes With Renal Artery Lesions) study were assessed for a rapid decline (RD) in estimated glomerular filtration rate (eGFR), defined as a ≥30% decrease from baseline to either 3 months, 6 months, or both. In the medical therapy–only cohort, eGFR was available in 359 subjects at all time points, the subjects were followed for a median of 4.72 years, and 66 of 359 (18%) subjects experienced an early RD. Baseline log cystatin C (odds ratio, 1.78 [1.11–2.85]; P =0.02), age (odds ratio, 1.04 [1.00–1.07]; P <0.05), and Chronic Kidney Disease Epidemiology Collaboration creatinine eGFR (odds ratio, 1.86 [1.15–3.0]; P =0.01) were associated with an early RD. Despite continued medical therapy only, the RD group had an improvement in eGFR at 1 year (6.9%; P =0.04). The RD and nondecline groups were not significantly different for clinical events and all‐cause mortality ( P =0.78 and P =0.76, respectively). Similarly, renal replacement therapy occurred in 1 of 66 (1.5%) of the RD patients and in 6 of 294 (2%) of the nondecline patients. The regression to the mean of improvement in eGFR at 1 year in the RD group was estimated at 5.8±7.1%. Conclusions: Early rapid declines in kidney function may occur in patients with renal artery stenosis when medical therapy is initiated, and their clinical outcomes are comparable to those without such a decline, when medical therapy only is continued. Abstract : See Editorial Beige